The use of perineal massagers and vaginal dilators as methods of physiotherapeutic treatment in Pelvic Dysfunctions: Vaginismus and Dyspareunia (Research, Society and Development, 2021)
Perineal massagers are manual therapeutic resources that are carried out through slips and myofascial releases in the pelvic region, stimulating the relaxation of the muscles and causing an inhibitory effect on muscular tensions, and the vaginal dilators soften the tissues and promote body awareness. The purpose of this article is to demonstrate how those of perineal massagers and vaginal dilators can be effective in the treatment of vaginismus and dyspareunia, based on research carried out through the digital platforms: Scielo, Pubmed and PEDro. It is concluded that in the face of vaginismus and dyspareunia pathologies, perineal massagers and vaginal dilators can be effective in the treatment by decreasing the perception of pain and muscle tension, recovering tone and promoting the desensitization of the pelvic floor muscles.